Evaluation of casing materials on productivity of milky mushroom (Calocybe indica P&C) - Chinara, Niranjan; Mahapatra, Shyam Sundar (Mushroom Research, 2022)
Milky mushroom (Calocybe indica P&C) is one of the important edible mushrooms cultivated in India. Its robust, fleshy, attractive colour with excellent keeping quality have made it popular among the edible mushrooms in recent times. It has the ability to grow on different agricultural wastes as well as high conversion rate. Hot and humid climate in coastal regions of India favours its large-scale cultivation. However, this mushroom has not yet been cultivated commercially in the state of Odisha. Different lignocellulosic materials are being used for production of milky mushroom but, casing materials used to induce the initiation of fruiting bodies, provide physical support and moisture to the mushroom. Therefore, eight different combination of casing materials were evaluated for productivity of milky mushroom in the Centre of Tropical Mushroom Research and Training, Odisha University of Agriculture and Technology, Bhubaneswar during the year 2018-19. From the result, maximum yield per bag 1146.7g with a biological efficiency of 76.5% was observed from the bags applied with loam soil:FYM (1:1) followed by vermicompost (1123.3g/bag). But, the bags with coir pith resulted lowest production (646.7g) than the bags without casing materials (873.3g).